2002
DOI: 10.1097/00007632-200212010-00008
|View full text |Cite
|
Sign up to set email alerts
|

COL9A3 Gene Polymorphism and Obesity in Intervertebral Disc Degeneration of the Lumbar Spine: Evidence of Gene-Environment Interaction

Abstract: The effect of obesity on lumbar disc degeneration seems to be modified by the collagen IX gene polymorphism, so that people who carry the Trp3 allele are at increased risk if they are persistently obese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 16 publications
0
68
0
2
Order By: Relevance
“…Manifestations of structural failure such as radial fissures, disc prolapse, endplate damage, internal or external collapse of the anulus, and disc narrowing can themselves be defined in pragmatic terms as is usual in the epidemiologic and radiologic literature. 65,113,114 Cell-mediated responses to structural failure can be regarded as the "final common pathway" of the disease process.…”
Section: Interpretation: What Is Disc Degeneration?mentioning
confidence: 99%
“…Manifestations of structural failure such as radial fissures, disc prolapse, endplate damage, internal or external collapse of the anulus, and disc narrowing can themselves be defined in pragmatic terms as is usual in the epidemiologic and radiologic literature. 65,113,114 Cell-mediated responses to structural failure can be regarded as the "final common pathway" of the disease process.…”
Section: Interpretation: What Is Disc Degeneration?mentioning
confidence: 99%
“…This scale resulted in a classification of degenerative disorders as non-existent, mild, moderate, and severe, respectively. In the 284 controls, 80.82% (230) were healthy with no disease, 12.68% (36) were diagnosed as having normal cardiovascular diseases and 6.50% (18) were diagnosed as having normal digestive system diseases, which were confirmed to be unconnected with intervertebral disease. The study was approved by the City Ethics Committee.…”
Section: Subjectsmentioning
confidence: 99%
“…Subsequent research revealed that a number of genes are associated with disc degeneration in human beings, including an aggrecan gene with shorter numbers of tandem repeat lengths; mutation genes coding for collagen IX (COL 9 A2 and COL 9 A3), and the matrix metalloproteinase-3 gene [14][15][16][17] . Solovieva 18) presented evidence suggesting that the effect of obesity on lumbar disc degeneration is modified by COL9A3 gene polymorphisms in Finnish men. These findings indicated that genetic risk factors may interact with environmental factors in exaggerating the development of disc degeneration.…”
mentioning
confidence: 99%
“…The aetiology of this disorder is unknown but may be due to the relative avascularity of the tissue, mineralization of or trauma to the cartilage endplate, mechanical factors, vertebral body microfracture and loss of notochordal cells. Whatever the exact pathway, disc degeneration is certainly associated with aging and has a strong genetic component [1,10,96,109,115,120]. The back pain that can develop either in association with or as a result of this disease has a lifetime prevalence of 80%.…”
Section: Introductionmentioning
confidence: 99%